Pembangunan Ekonomi dalam Prespektif Islam: (Satu Analisis Pesantren Gontor dalam Memberdayakan Ekonomi Masyarakat) - Syamsuri Syamsuri (University of Darussalam Gontor, 2016)
Pesantren is an educational institution that was born out of the historycal product having relasition whith the coming of Islam into the archipelago. Its presence has provided a new model for the life of Indonesian society in particular. Be it in the form of socio-political, socio-cultural, socio-economic and socio-religious. in this case it is happens because schools were created rather than the hopes and ideals of society that makes the moral values of Islam as the foundation concepts and motivation charity. It is no exaggeration if the orientation of the establishment of pesantren to spawned man a dedicated to the community and have the personality of the Prophet. As self-sufficient, have a noble and beneficial to society. Gontor has exists since 90 years ago, at least has positioned itself at strategic places, namely; become an institution of religious knowledge development, a seedbed of human resources, and institutional economic development. Economic development here is intends a comprehensive development (multi-dimensional) which covers various aspects; physical, spiritual or moral. The principle of the implementation of human empowerment is based on the concept of tauhid and aims at gaining God’s pleasant (redho Allah s.w.t.). This study used a qualitative case study method with three data collection techniques, such as observation, interviews and documentation in Pesantren Gontor Ponorogo Indonesia. This paper will present how strategy pesantren Gontor in empowering the community, and the extent of its role in economic development based on Islam.